Ephedorae herba Decreases Lipopolysaccharide-Induced Cyclooxgenase-2 Protein Expression and NF-κB-Dependent Transcription in C6 Rat Glioma Cells - Kohichi Aoki; Tohru Yamakuni; Masaaki Yoshida; Yasushi Ohizumi (Elsevier, 2005)
We studied the effects of Mao (Ephedrae herba) on lipopolysaccharide (LPS)-induced expression of inducible cyclooxygenase (COX-2) in C6 rat glioma cells. Western blot analysis showed that Mao inhibited LPS-induced expression of COX-2 protein, but not that of constitutive cyclooxygenase. Reporter gene assays showed that Mao reduced LPS-inducible NF-κB-dependent transcription that plays a crucial role in induction of COX-2 gene expression. This crude drug decreased LPS-induced IκBα degradation in a concentration-dependent manner without affecting LPS-induced IκB phosphorylation. These results suggest that Mao prevents LPS-induced NF-κB-dependent transcription by inhibiting IκB degradation and suppresses an increase in COX-2 protein expression in C6 cells. Keywords:: Ephedrae herba, COX-2 gene expression, NF-κB-dependent transcription